Optimizing Collagenase, Fetal Bovine Serum, and Insulin to Isolate, Proliferate, and Differentiate Rat Preadipocyte in vitro - Indra, M Rasjad; Satuman, Satuman; Widodo, Edwin (Jurnal Kedokteran YARSI, 2008)
BackgroundThe aim of this study is to develop a method for optimal in vitro proliferation and differentiation of rat adipocyte. MethodsPreadipocyte were isolated from omentum of Rattus norvegicus Wistar using Collagenase type I dan II (Sigma). Cells were cultured in M199 culture containing either 0%, 8% or 10% Fetal Bovine Serum (FBS). Insulin were added into the media once the cells attached to the culture plate Proliferating and differentiated cells were counted and analysed by using Oil Red O dan Hematoxylen (HE) staining. Results This study demonstrated that adipocyte could be isolated using Collagenase type I but not type II. The addition of 10% FBSsignificantly increased the number of preadipocyte and differentiation of adipocyte more than those of 8% FBS and without FBS. The timing of FBS addition was best performed on day 8 using 10% FBS. Specific adipocyte staining using Oil Red O revealed thatthere were core lipids in mature adipocyte. ConclusionsCollagenase tipe I could be used to isolate preadipocyte cells. Supplementation of culture media with 8-10% FBS could enhance the in vitro proliferation of preadipocyte. Standard media M199 containing 10% FBS and insulin may provide an environment to differentiate preadipocyte specifically into adipocyte in vitro.